Study on Characteristics of Ash Accumulation During Co-Combustion of Salix Biomass and Coal - Yan Zhang; Chengzhe Shen; Dongxv Wang; Jinbao Zhang; Kai Yang; Haisong Yang; Hailong Liu; Xintong Wen; Yong Zhang; Yunhao Shao; Ruyu Yan; Ningzhu Ye; et al. (Energies)
Co-combustion of coal and biomass for power generation technology could not only realize the effective utilization of biomass energy, but also reduce the emission of greenhouse gases. In this study, a system of a settling furnace with high temperature is applied to study the ash deposition of the co-combustion of coal and salix. The effects of salix blending ratio, flue gas temperature, and wall temperature on ash deposition are studied. The micro-morphology, elemental content, and compound composition of the ash samples are characterized by scanning electron microscopy and energy-dispersive spectroscopy (SEM-EDS) and X-Ray Diffraction (XRD), respectively. The results show that with the biomass blending ratio increasing from 5% to 30%, the content of Ca in ash increases from 8.92% to 20.59%. In particular, when the salix blending ratio exceeds 20%, plenty of the low-melting-point compounds of Ca aggravate the melting adhesion of ash particles, causing serious ash accumulation. Therefore, the salix blending radio is recommended to be limited to no more than 20%. With the increase in flue gas temperature, ash particles melt and stick, forming ash accumulation. Under the condition of flue gas temperature ≥ 1200 °C, a serious ash particle melting flow occurs, and CaO covers the surface of the ash particles, making the ash particles adhere to each other, which makes them difficult to remove. Therefore, controlling the flue gas temperature below 1200 °C is necessary. When the temperature crosses the threshold range of 500–600 °C, the Ca and K contents increase by 35.6% and 41.9%, respectively, while the Si content decreases by 9.7%. The increase in K and Ca content leads to the thickening of the initial layer of the ash deposit, which facilitates the formation of the sintered layer of the deposited ash. Meanwhile, the reduction in Si content leads to the particles’ adhesion, which markedly increases the degree of ash slagging. Once the wall temperature exceeds 600 °C, severe ash slagging becomes a threat to the safe operation of the boiler. Therefore, the wall temperature should not exceed 600 °C.